ANALISIS PELAKSANAAN EVALUASI PEMBELAJARAN BIOLOGI KELAS X SEMESTER GENAP 2013/2014 DI SMAN KOTA BLITAR - Hasanah, Umi; Prasetyo, Triastono Imam; Lukiati, Betty (Universitas Negeri Malang, 2015)
The results showed that the evaluation implementation of learning in senior high school 1 Blitar was appropriate curriculum in 2013, but the teacher in senior high school in 1 Blitar must to complete assessment instruments portofolio, practice tests and tests. The evaluation implementation of learning in senior high school 2 Blitar appropriate curriculum 2013 is the assessment of the attitude with observation, assessment practice test and a written test, but all of implementation assessment instrument not yet, so the teacher must to complete the assessment instrument. Evaluation implementation of learning in senior high school 4 Blitar appropriate curriculum 2013 is the assessment of the attitude with observation, assessment written test, portofolio, practice tests and projects. Same as senior high school 1, the teacher must to complete assessment instrument portofolio, practice test and project.